Optimization of steel structures with one genetic algorithm according to three international building codes - Prendes-Gero , María-Belén; Bello-García, Antonio; del Coz-Díaz, Juan-José; Suárez-Domínguez, Francisco-José; García Nieto, Paulino-José (Revista de la Construcción. Journal of Construction, 2018)
Among all the optimization techniques, the genetic algorithms (GAs) stand out because of their mathematical simplicity, the no necessity of information about the objective function or the constraint functions, and the possibility of working with any type of structure. Although these features suggest an enormous flexibility for working with different building codes, in general, each one is developed for a particular structure and a particular building code. In a world without borders, where one structure can be calculated in one country, manufactured in other and built in a third one, develop one GA for each building code difficult the construction process and increase its cost. In this paper, one GA capable of working with three different building codes (Spanish, European and American) is researched. After analysing the different constraints and stabilities for them, the objective function is defined. Then, and due the influence that the working parameters have in the optimization result, the effect of each parameter over the behaviour of the GA is analysed and a working range for them is established. Finally, the results of the optimization are compared, showing the heaviest structures with the American code and the lightest structures with the European code.